Czech language acquisition seen by a Russian-speaking learner - J. Kovářová (Вестник Северо-Кавказского федерального университета, 2022)
The paper discusses teaching Czech language to Russian speaking adolescent learners. The article is based on a research which focuses on the learners´ subjective perception of their second language acquisition. The topic, i. e. subjective perception of Czech language acquisition, has not been researched in detail yet. In our opinion, the topic is important, though, as the learner´s subjective perception strongly affects the success of teaching. The research findings are based on semi-structured in-depth interviews with Russian speaking learners. The crucial findings are as follows: low metacognition among adolescent learners, predominantly passive approach towards second language acquisition and (subjectively perceived) demanding nature of oral language skills. At the end of the article some general didactic suggestions are offered.